Título Padrão: Tartarugas marinhas encalhadas na costa de Fortaleza, Ceará, Brasil, e implicações para a conservação do táxon - Frota Feitosa, Alice; Melo Mendonça, Débora; Ben Hur Moreira Pinto Menêzes, Ícaro; Xavier Rufino, Ruama Catarina; Rosa Sousa Carvalho, Lidya; Rabelo de Castro Sousa, Rodrigo; Chagas Lima, Gabriel; Vieira Feitosa, Caroline (Arquivos de Ciências do Mar, 2022)
The Ceará’s state coast belongs to one of the most important areas of the South Atlantic for migration and feeding of sea turtles. Thus, the present study observed (1) which species occur in Fortaleza, (2) which species and sex are beached the most, (3) the life stage and (4) season that they most strand. We aimed to update existing information regarding the occurrence of sea turtles in Fortaleza, evaluate if seasonality influences beaching behavior, register the beached species on the coast of Fortaleza, and investigate the beaching behavior. This study was carried out in Fortaleza, Brazil. Data were obtained through monitoring and reports provided by the local community, from January/16 to December/19. A total of 112 beached turtles of four species were observed, and younger specimens were more observed. No significant differences appeared between the years, months, and the rainy/dry seasons on the number of the strandings. Females were observed more than males for all species, perhaps due to the use of the region as a migratory route for breeding and foraging. This is the first data for Ceará State published in a scientific paper, which can be used as the basis to raise awareness in the general population, and government, regarding the vulnerability of these organisms. Keywords: Chelonia mydas, juvenile turtles, female turtles, human activities, northeastern.